Analogical Reasoning in Children With Autism Spectrum Disorder: Evidence From an Eye-Tracking Approach - Tan, Enda; Wu, Xueyuan; Nishida, Tracy; Huang, Dan; Chen, Zhe; Yi, Li (Frontiers in Psychology, 2018)
The present study examined analogical reasoning in children with autism spectrum disorder (ASD) and its relationship with cognitive and executive functioning and processing strategies. Our findings showed that although children with ASD were less competent in solving analogical problems than typically developing children, this inferior performance was attributable to general cognitive impairments. Eye-movement analyses revealed that children with ASD paid less attention to relational items and showed fewer gaze shifts between relational locations. Nevertheless, these eye-movement patterns did not predict autistic children’s behavioral performance. Together, our findings suggest that ASD per se does not entail impairments in analogical reasoning. The inferior performance of autistic children on analogical reasoning tasks is attributable to deficits in general cognitive and executive functioning.